Wetlands in Your County: Alachua - Mark W. Clark; Stacie Greco; Susan Curry (EDIS, 2010)
SL307, a 5-page illustrated fact sheet by Mark W. Clark, Stacie Greco, and Susan Curry, provides specific information about wetlands in Alachua County. Published by the UF Department of Soil and Water Sciences, December 2009.